ANALISIS PROGRAM SEHATI TERHADAP AKSELERASI INDUSTRI HALAL DI WISATA RELIGI SUNAN DRAJAT LAMONGAN - Fithrotin; Khurul Aimmatul Umah; Vika Madinatul Ilmi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This research aims to accelerate the development of the halal industry in the Sunan Drajat Paciran Religious Tourism area, Lamongan, through the assistance of the selfdeclare program. The activities are focused on Micro and Small Enterprises (MSEs) which have great potential in the religious tourism sector and the halal economy. The Community-Based Research (CBR). The results of the assistance show an increased understanding of MSE actors about the importance of halal certification. In addition, this program has succeeded in strengthening local product branding and opening access to a wider market. Obstacles found include a lack of understanding of the halal concept and limited human resources. This research contributes to the improvement of MSE competitiveness and the development of inclusive halal tourism.